Quantifying relative within-host replication fitness in influenza virus competition experiments. (7th October 2015) - Petrie, Stephen M.; Butler, Jeff; Barr, Ian G.; McVernon, Jodie; Hurt, Aeron C.; McCaw, James M.
Abstract: Through accumulation of genetic mutations in the neuraminidase gene, the influenza virus can become resistant to antiviral drugs such as oseltamivir. Quantifying the fitness of emergent drug-resistant influenza viruses, relative to contemporary circulating viruses, provides valuable information to complement existing efforts in the surveillance of drug-resistance. We have previously developed a co-infection based method for the assessment of the relative in vivo fitness of two competing viruses. We have also introduced a model of within-host co-infection dynamics that enables relative within-host fitness to be quantified in these competitive-mixtures experiments. The model assumed that fitness differences between co-infecting strains were mediated by strain-dependent viral production rates from infected epithelial cells. Here we extend the model to enable a more complete exploration of biological processes that may differ between virus pairs and hence generate fitness differences. We use the extended model to re-analyse data from competitive-mixtures experiments that investigated the fitness of oseltamivir-resistant (OR) H1N1 pandemic 2009 ("H1N1pdm09") viruses that emerged during a community outbreak in Australia in 2011. Results are consistent with those of our previous analysis, suggesting that the within-host replication fitness of these OR viruses is not compromised relative to that of related oseltamivir-susceptible (OS) strains, and that potentially permissive mutations in the neuraminidase gene (V241I and N369K) significantly enhance the fitness of H1N1pdm09 OR viruses. These results are consistent regardless of the hypothesised biological cause of fitness difference. Abstract : Highlights: Influenza viral fitness can be probed using in vivo co-infection experiments. We use a within-host model of such experiments to quantify relative fitness. Different assumptions for the biological cause of fitness difference are explored. Certain neuraminidase mutations enhance the fitness of drug-resistant influenza. Our findings are consistent regardless of the assumed cause of fitness difference.